The Influence Of Forehand Grip Handling And Backhand Grip On Short Service Ability In Badminton Of Collage Students - Jufri Jufri; Ruslan Ruslan; Rahmadi Rahmadi (UNIB Press, 2020)
This study aims to determine the effect of the handle on the short service ability of badminton games in Penjaskesrek students. This research is a pre-experiment, namely tow Group pretest-posttest design, the population in the study were 40 students of Physical Education Class 2017, Mulawarman University Samarinda. The data collection technique uses a short service test instrument, namely the forehand grip service test grip and the backhand grip handle. Based on the data analysis, the results obtained from the pretest average value of the forehand grip grip ability of 32.3500, the average posttest value of the forehand grip grip of 52.6000, the value of t count> is 7.818, the significance value of the probability is 0.000, and the t table is 2.818. and the mean value of the backhand grip pre-test ability of 32.1500, the average value of the backhand grip posttest of 48.1000, the value of t count> of 10,747, the significance value of the probability of 0.000, and the t table of 2,746. the value of t table 0.050 is greater than t count 0.025 and the value of sig <a (0.000 <0.05), so it can be seen that Ho is accepted and H1 is accepted. This means that there is a significant effect of the effect of the forehand grip and the backhand grip of badminton on students by 95%.